PENYELESAIAN SENGKETA DALAM KEWARISAN ADAT DALAM PERSPEKTIF HUKUM ISLAM - Rukiah Rukiah; Herman Herman (DIKTUM: Jurnal Syariah dan Hukum, 2011)
This paper describes the customary inheritance dispute resolution in the perspective of Islamic law. The analytical method used is descriptive qualitative analysis, which include: 1) inductive method, 2) Method deductive, and 3) The comparative method. Discussion of the results obtained by the understanding that: Based on the results of data analysis and discussion of results of qualitative descriptive research for one month, then it can be summed up as follows; System inheritance garden in the District Maiwa Enrekang is basically deliberation, in consultation division two, the system of inheritance heir died before and after heir dies. The process of inheritance to the heir was still alive at the time Maiwa society can be implemented in a way instructed or intestate. Inheritance Heir Dies After implemented in two ways such a calculation fiqhi Islamic inheritance, which in this division of the boys doubles and girls the same way ma'bage mana’ (flat share), where the boys and women's equal and balanced. This is done because according to the District Maiwa Enrekang that this system is a way to get justice among all heirs. In the perspective of Islamic law such a way that does not conflict with the nature and objectives of Islamic law which is to create peace and tranquility, as described in the verses of the Quran and the Hadith of the Prophet.